Information Technologies and Business Value: An Analytic and Empirical Investigation - Barua, Anitesh; Kriebel, Charles H.; Mukhopadhyay, Tridas (Information Systems Research, 1995)
An important management question today is whether the anticipated economic benefits of Information Technology (IT) are being realized. In this paper, we consider this problem to be measurement related, and propose and test a new process-oriented methodology for ex post measurement to audit IT impacts on a strategic business unit (SBU) or profit center's performance. The IT impacts on a given SBU are measured relative to a group of SBUs in the industry. The methodology involves a two-stage analysis of intermediate and higher level output variables that also accounts for industry and economy wide exogenous variables for tracing and measuring IT contributions. The data for testing the proposed model were obtained from SBUs in the manufacturing sector. Our results show significant positive impacts of IT at the intermediate level. The theoretical contribution of the study is a methodology that attempts to circumvent some of the measurement problems in this domain. It also provides a practical management tool to address the question of why (or why not) certain IT impacts occur. Additionally, through its process orientation, the suggested approach highlights key variables that may require managerial attention and subsequent action.